Evaluation of Complications of Spinal Anesthesia- A Clinical Study - Lamba, Kapil (Academia Anesthesiologica International, 2019)
Background: Spinal anaesthesia is one of the most popular and widely used anaesthetic procedures. The present study was conducted to evaluate complications of spinal anesthesia during cesarean section. Subjects and Methods: The present study was conducted in the department of Anesthesiology. It comprised of 78 patients who reported complications in operation theatre during cesarean section. Intraoperative complications such as nausea/ vomiting, hypotension, backache, high spinal block, post-dural puncture headache (PDPH), loss of consciousness, shivering and anesthetic failure was determined. Results: Age group 20-24 years had 28 patients, 24-28 years had 30 and 28- 32 years had 20 patients. The difference was significant (P< 0.05). The most common complication was shivering seen in 38, nausea/vomiting in 32, anesthetic failure in 15, post-dural puncture headache (PDPH) in 14, hypotension in 18, high spinal block in 10, backache in 8 and loss of consciousness in 2. The difference was significant (P< 0.05). Conclusion: Author found that complications of spinal anesthesia vary in different situations. Common complication was shivering, anesthetic failure, Post-dural puncture headache (PDPH), hypotension, nausea, vomiting, high spinal block, backache and loss of consciousness.